SEDIMENT YIELD ESTIMATES IN NORTH-WESTERN GREECE AND ANALYSES WITH HYDROLOGIC AND GEOMORPHOLOGIC FACTORS - Zarris, D.; Lykoudi, E.; Panagoulia, D. (Bulletin of the Geological Society of Greece, 2007)
Erosion and sediment yield form a crucial issue within the integrated water resources management context; however are often neglected during the design of major water systems. Sediment yields in 11 river catchments in North-Western Greece are computed with the application of the mean daily discharges to the sediment discharge rating curves and compared to the earlier estimates published by other researchers. For these catchments a number of hydrologie and géomorphologie parameters have been computed using advanced mapping methodologies. An attempt is made to correlate the suspended sediment estimates mainly with géomorphologic parameters, that rarely has been carried out in the international literature.